1996
DOI: 10.1080/15428119691014279
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Assessment for a Field Investigation of the Acute Respiratory Effects of Metalworking Fluids. I. Summary of Findings

Abstract: The exposure assessment summarized here is part of an epidemiologic study of the acute respiratory health effects of metalworking fluid (MF) exposures. Exposures were measured as the inhalable concentrations of the MF aerosol, a variety of metals and elements, and endotoxin as well as the level of culturable bacteria in the aerosol size fraction less than 8 microns. Bulk samples of soluble MFs were tested for pH, mineral and tramp oil fraction, endotoxin, culturable bacteria, and lipopolysaccharide levels. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…According to Laitinen et al [5], average concentrations of viable bacteria equalled from 10 5 to 10 8 CFU/ml, with the highest concentration level of 10 10 CFU/ml. Similar ranges are also quoted by Woskie et al [14] and Foxal-VanAken et al [15]. The coolants examined were considerably less contaminated with moulds.…”
Section: Discussionsupporting
confidence: 77%
“…According to Laitinen et al [5], average concentrations of viable bacteria equalled from 10 5 to 10 8 CFU/ml, with the highest concentration level of 10 10 CFU/ml. Similar ranges are also quoted by Woskie et al [14] and Foxal-VanAken et al [15]. The coolants examined were considerably less contaminated with moulds.…”
Section: Discussionsupporting
confidence: 77%
“…The authors could identify no clear relationships between measures of contamination and airborne exposure. In addition, despite the obvious presence of hypersensitivity pneumonitis, no association with any single organism could be identi®ed, although the range of organisms resembled that of other reports [Rossmore, 1981;Mattsby-Balzer et al, 1989;Lummus et al, 1998] and similar exposures were identi®ed [Thorne et al, 1996;Woskie et al, 1996]. Despite intense and aggressive searching, no evidence supported Mycobacterium chelonae as a cause of this outbreak.…”
Section: Discussionmentioning
confidence: 51%
“…Worse, 6% of the sumps examined in this study had never been cleaned or had MWF completely replaced. Interestingly, Woskie et al (1996) were able to investigate this issue, but found that pH, tramp oil concentration and endotoxin concentrations were not affected by how recently soluble sump fluids were changed (<4 days, 4-21 days, >21 days).…”
Section: A Model To Predict Mwf Sump Endotoxin Concentrationsmentioning
confidence: 99%
“…Milton and Johnson (1995) reported a range of sump endotoxin concentrations of 13 100-124 000 EU/ml in two automotive plants. Woskie et al (1996) conducted a study in automotive parts manufacturing facilities where machines had independent sump systems and were run intermittently. The GM MWF sump endotoxin concentration was 39 000 EU/ml.…”
Section: Mwf Sump Endotoxin Concentrationsmentioning
confidence: 99%